KAJIAN KARAKTERISTIK HABITAT RAFFLESIA (Rafflesia patma BLUME.) DI CAGAR ALAM BOJONGLARANG JAYANTI, CIANJUR, JAWA BARAT - Muhammad Adlan Ali; Agus Hikmat; Ervizal AM Zuhud (Media Konservasi, 2015)
Bojonglarang Jayanti Nature Reserve one of habitat Rafflesia patma. The purpose of this research  to identify biotic and abiotic habitat characteristic of R. patma in Bojonglarang Jayanti Nature Reserve. Research conducted in March until April, using single plot analysis habitat to take physical and biotic data as well as the study of literature for climate data retrieval. R. patma habitat have lowland and coastal forest vegetation types  with dominant species Cyathocalys biovulatus. Fauna that be a benefit to the life of Rafflesia are 19 species from 15 Family. There are 90 individual R.patma found at altitude 0-100 m above sea level, slope average 14.73%, the distance from the coast beach 758 m, a distance from the water 12 m, litter thickness 1.7 cm, and the type of soil is Podsolic with low nutrient content and acidic pH. R. patma habitat has C climate type.  Key word : Abiotic, Biotic, Habitat, Population, R. Patma